Fisher Boncalang Technology Implementation for Productivity Improvement and Product Diversification of Bettet Village MSMEs - Suli Da'im; Moh Ali; Dina Novita; Nova Elok Mardliyana; Anastas Rizaly; Dina Mulyana Firdausiyah (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2026)
Background: This community service program was designed to address the challenges faced by the PKK Bettet MSME group, including low productivity, inconsistent product quality, inadequate packaging, and limited marketing capacity. The main objective was to enhance the competitiveness of local MSMEs through the integration of technological innovation, hygienic processing, improve packaging, and digital marketing. Contribution: The program contributed to empowering rural women’s groups through the introduction of the Fisher Boncalang fish shredder, improved packaging practices, product diversification, and digital marketing skills, thereby forming an integrated empowerment model Method: The program was implemented in five stages: socialization, training, technology application, mentoring and evaluation, and sustainability planning. Results: The results indicate a significant increase in production capacity, rising from 1 kg per 5 hours to 15–50 kg per hour. Product quality also improved through the implementation of standardized packaging, which extended the shelf life from 3–5 days to 1–2 months. Conclusion: The program achieved its objectives by integrating technology, training, and marketing. These results show that MSME empowerment through innovation and digitalization can enhance productivity, product competitiveness, and sustainable rural entrepreneurship.